Children's house designing a child-centered non-formal learning center - Fabon, Marie Eirene F. (College of Architecture, University of the Philippines Diliman, 2019)
Education is a basic human right yet we all know that not everyone can exercise this right. While basic public education is offered for free in the country, a large percentage of children in the country is considered out-of-school due to three main reasons: family problems, poverty, and lack of interest. As a response to these issues, providing an alternative to traditional education which offers a non-formal learning allowing for intermittent learning schedule and also providing a child-centered approach can be a solution in making education more accessible to those who can't attend traditional education.